Growth, chlorophyll content and yield of maize and banana plants in an agroforestry system in Kisii County, Kenya - Wafula, Dickrecious; Mutisya, Musyimi David; Anyango, Phoebe Sikuku (Current Research in Agricultural Sciences, 2023)
Diverse tree species when employed in agroforestry systems may serve as an alternative to increasing soil fertility through nitrogen fixation. However, it is not clearly known how intercropping maize and banana with Sesbania sesban, Calliandra callothyrsus and Leucaena diversifolia may affect growth of maize and banana. The purpose of this study was to evaluate the effect of intercropping agroforestry trees species with maize and banana on the growth, chlorophyll content and yield of maize and banana. Field experiment was laid out at Kenya Agricultural Livestock and Research Organization farm (KALRO) located in Kisii County. The Williams varieties of banana of the same age were obtained from KALRO -Thika and Hybrid seed maize, H513 obtained from Kenya seed company, Kisumu. The agroforestry tree seedlings were spaced: 0.5m by 1m, 0.9m by 0.9m by 0.6m deep and 0.3m by 0.75m between banana and maize respectively. Three replicates were used with seven treatments of Pure maize, pure banana, maize-banana-Calliandra, maize-banana-Leucaena, maize-banana-sesbania, maize-banana and maize-fertilizer, all in a randomized complete block design. Data on maize growth and chlorophyll content was collected at intervals of 2 weeks which commenced 30 days after planting while yield was determined at the end of growing seasons. Data was subjected to the Analysis of Variance. Maize plants and banana that were intercropped with Sesbania sesban had significantly (P≤0.05) highest growth, chlorophyll content and yield compared to other treatments. Therefore, Sesbania sesban is recommended as a suitable agroforestry tree species for intercropping with maize and bananas.